Menakar Akses Keadilan bagi Korban Kekerasan Fisik Mahasiswa: Tinjauan Ilmu Viktimologi - Gifari Gifari; Josua Josua; Danu Danu; Dzulfikar Dzulfikar; Adi Adi; Melati Melati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Violence among university students is a serious issue that often neglects the position of victims as subjects who deserve legal and social protection. The case of mob violence against a law faculty student at Sultan Ageng Tirtayasa University (Untirta) in SMKN 2 Serang City in June 2024 reveals the complexities of victims’ access to justice, marked by slow legal processes and insufficient institutional support. This study employs a qualitative approach with a normative empirical juridical legal research design and a case study method, combining an examination of legislation with field data to explore the social, legal, and psychological conditions of the victims through semi-structured interviews, document analysis, and literature review. Data analysis is conducted descriptively-analytically using thematic coding and source triangulation to ensure the validity of findings. The study uncovers three main findings: (1) secondary victimization experienced by victims due to legal process stagnation and lack of accompaniment, (2) institutional responses prioritizing campus reputation over victim recovery, and (3) a culture of violence normalizing violent acts as internal campus conflicts. This research offers victimology-based recommendations, including the establishment of victim service units on campus, sensitivity training for law enforcement officers, and revisions to victim-centered campus policies. The findings underscore the importance of a victimological approach in supporting restorative justice for student violence victims.